Characterizing blood–brain barrier perturbations after exposure to human triglyceride‐rich lipoprotein lipolysis products using MRI in a rat model. Issue 4 (20th October 2015) - Ng, Kit Fai; Anderson, Steve; Mayo, Patrice; Aung, Hnin Hnin; Walton, Jeffrey H.; Rutledge, John C.
Abstract : Purpose: Previous studies indicated hyperlipidemia may be a risk factor for Alzheimer's disease, but the contributions of postprandial triglyceride‐rich lipoprotein (TGRL) are not known. In this study, changes in blood–brain barrier diffusional transport following exposure to human TGRL lipolysis products were studied using MRI in a rat model. Methods: Male Sprague‐Dawley rats (∼180–250 g) received an i.v. injection of lipoprotein lipase (LpL)‐hydrolyzed TGRL (n = 8, plasma concentration ≈ 150 mg human TGRL/dL). Controls received i.v. injection of either saline (n = 6) or LpL only (n = 6). The 1 H longitudinal relaxation rate R1  = 1/T1 was measured over 18 min using a rapid‐acquired refocus‐echo (RARE) sequence after each of three injections of the contrast agent Gd‐DTPA. Patlak plots were generated for each pixel yielding blood‐to‐brain transfer coefficients, Ki, chosen for best fit to impermeable, uni‐directional influx or bi‐directional flux models using the F‐test. Results: Analysis from a 2‐mm slice, 2‐mm rostral to the bregma showed a 275% increase of mean Ki during the first 20 min after infusion of human TGRL lipolysis product that differed significantly compared with saline and LpL controls. This difference disappeared by 40 min mark. Conclusion: These results suggest human TGRL lipolysis products can lead to a transient increase in rat BBB permeability. Magn Reson Med 76:1246–1251, 2016. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.